2020
DOI: 10.1002/1438-390x.12068
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the maximum sustainable yield of snow crab (Chionoecetes opilio) off Tohoku, Japan via a state‐space stock assessment model with time‐varying natural mortality

Abstract: A maximum sustainable yield (MSY) obtained by maintaining or restoring fish stock levels is a tangible benefit of ecosystem services. Snow crab (Chionoecetes opilio) off Tohoku, Japan has been managed by a total allowable catch since 1996, although the abundance has not increased. Surprisingly, there was no increase after 2011, when fishing pressure was greatly reduced because of the Great East Japan earthquake. This implies that some of the crab's biological characteristics, such as recruits, natural mortalit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…The snow crab is an important commercial fishing resource off the coast of Tohoku. Surprisingly, Shibata et al (2020) found that the abundance of this crab was unchanged after the 2011 tsunamis, even though fishing was banned for several years after the GEJE. The study provided evidence that the snow crab populations off Tohoku may have suffered from other sources of mortality, such as warming and predation.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The snow crab is an important commercial fishing resource off the coast of Tohoku. Surprisingly, Shibata et al (2020) found that the abundance of this crab was unchanged after the 2011 tsunamis, even though fishing was banned for several years after the GEJE. The study provided evidence that the snow crab populations off Tohoku may have suffered from other sources of mortality, such as warming and predation.…”
mentioning
confidence: 98%
“…They also cautioned the possibility that, although the tsunamis' impact was a temporary event, the abundance of this porpoise species may continue to decline in the future due to human-induced threats such as fisheries bycatch. Shibata et al (2020) also examined offshore animals, but those living on the sea floor, that is, snow crab (Zuwai-gani in Japanese). The snow crab is an important commercial fishing resource off the coast of Tohoku.…”
mentioning
confidence: 99%
“…The next two papers (Nishijima et al, 2021; Shibata et al, 2021) focus on temporally variable biological parameters of specific fisheries stocks around Japan. Nishijima et al (2021) reveal regime shifts in the productivity of Japanese flying squid ( Todarodes pacificus ) stocks using a multi‐stock modeling approach.…”
mentioning
confidence: 99%
“…Nishijima et al (2021) reveal regime shifts in the productivity of Japanese flying squid ( Todarodes pacificus ) stocks using a multi‐stock modeling approach. Shibata et al (2021) infer that a recent increase in natural mortality of snow crab ( Chionoecetes opilio ) has drastically changed maximum sustainable yield. Both studies use their tailor‐made state‐space models for stock assessment, with the advanced techniques able to capture the dynamic nature of fisheries resources in a changing environment.…”
mentioning
confidence: 99%
See 1 more Smart Citation